Fat talk frequency in high school women: Changes associated with participation in the Body Project. (September 2020) - Vanderkruik, Rachel; Conte, Isabella; Dimidjian, Sona
Highlights: Body Project participants experienced a significant reduction in fat talk frequency. Body Project participants reported significant reduction in family fat talk. Change in fat talk frequency is associated with change in weight concerns. Abstract: The Body Project is an evidence-based eating disorder prevention program that aims to prevent the onset of eating disorders by challenging the thin-ideal and promoting body acceptance through dissonance-based activities. One of the key program targets is fat talk, the self-deprecating communication about dissatisfaction with one's weight and shape. Fat talk, family fat talk, and weight concern are associated with body image disturbance and eating disorder development, especially in adolescent girls. Despite this, there is a gap in the research that specifically evaluates the extent to which participation in the Body Project changes fat talk frequency. In the current study, we examined change in fat talk frequency, family fat talk frequency, and weight concern among high school-aged women who participated in the peer-led Body Project. A total of 112 female students completed baseline assessments and 105 participants completed the post-intervention assessment measures for an 94 % response rate. The majority of participants (83 %) identified as Caucasian/White and ages ranged from 15 to 18 years of age. Results found that participation in the Body Project was associated with decreases in self-reported fat talk frequency, family fat talk frequency and weight concern. We discuss possible explanations for these findings and future research directions.